Causal Relationships Between Osteoarthritis and Senile Central Nerve System Dysfunction: A Bidirectional Two-Sample Mendelian Randomization Study - Cai, Yuanqing; Zhang, Guangyang; Liang, Jialin; Jing, Zhaopu; Zhang, Rupeng; Lv, Leifeng; Dang, Xiaoqian (Frontiers in Aging Neuroscience, 2022)
Background: The relationship between senile central nervous system dysfunctions (CNSDs), including Parkinson's disease (PD), Alzheimer's disease (AD), and ischemic stroke (IS), and osteoarthritis (OA), has gradually attracted attention. At present, the causal relationship between CNSD and OA remains unclear. The aim of this study was to assess the causal effects of CNSD and OA using Mendelian randomization (MR). Methods: Genome-wide association study (GWAS) summary data for CNSD and OA were obtained. Single nucleotide polymorphisms (SNPs) were selected as instrumental variables (IVs), and significant (P < 5.0×10-8) and independent (r2 < 0.1) SNPs were extracted for bidirectional MR analysis. Inverse variance weighted (IVW) was used to assess these causal relationships. The results are reported as odds ratios (ORs). Subsequently, heterogeneity was tested using Cochran’s Q test and pleiotropy by MR-Egger intercept, and sensitivity analysis was performed using the leave-one-out sensitivity test. Results: The MR results of the causal relationship between PD and OA showed that there was a positive causal effect of OA on PD, which was estimated by inverse variance weighted (IVW) [OR=1.194, 95%CI=1.036, 1.378; P=0.0144). Moreover, the MR analysis by IVW also showed that IS had a positive effect on OA (OR= 1.033, 95%CI= 1.002, 1.066; P= 0.0355). These results are reliable and stable, as confirmed by sensitivity tests. Conclusion: In total, the present study showed a positive causal effect of OA on PD, but there was a null effect of OA on AD, such as OA on IS.